Pengendalian Hemodinamik Intraoperatif pada Pasien Tumor Adrenal Fungsional yang Menjalani Adrenalektomi - Adiyanto, Bowo; Widodo, Untung; Sutiyoso, Noor Aditya (Jurnal Komplikasi Anestesi, 2022)
Adrenal gland surgery needs a multidisciplinary team including endocrinologist, radiologist, anesthesiologist, and surgeon. The indications for adrenal gland surgery include hormonal secreting and non-hormonal secreting tumors. Adrenal hormonal secreting tumors present to the anesthesiologist unique challenges requiring good preoperative evaluation, perioperative hemodynamic control, corrections of all electrolytes and metabolic abnormalities, a detailed and careful anesthetic strategy, overall knowledge about the specific diseases, control and maintaining of postoperative adrenal function, and finally a good collaboration with other involved colleagues.